Thalamic Bursts Down-regulate Cortical Theta and Nociceptive Behavior - LeBlanc, Brian W. (Sci Rep, 2017)
We tested the relation between pain behavior, theta (4–8 Hz) oscillations in somatosensory cortex and burst firing in thalamic neurons in vivo. Optically-induced thalamic bursts attenuated cortical theta and mechanical allodynia. It is proposed that thalamic bursts are an adaptive response to pain that de-synchronizes cortical theta and decreases sensory salience.